Assesment Kurikulum Merdeka Belajar di Sekolah Menengah Atas - Muliana GH; Andi Sadriani; Zuhrah Adminira (Peneliti.net, 2023)
Assessment is a whole process that is generally used in assessing and reviewing student performance, both in terms of cognitive, affective and psychomotor. Assessment is the process of collecting data that shows the development of student learning. The research method used is descriptive qualitative method by collecting data through literature study. The results of the study stated that authentic assessment aims to measure student development in affective, cognitive, and psychomotor aspects. The independent learning curriculum has learning content that is summarized to be more optimal, so that students have sufficient time to explore concepts and strengthen the competencies possessed by students.